Comparing the Performance of Cattle Castrated Using Different Techniques Upon Arrival at the Feedlot - Tyler Blackwood; Tyler J. Spore; Michael D. Kleinhenz; William R. Hollenbeck; Dale A. Blasi; A. J. Tarpoff (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:To determine the least detrimental castration technique in terms of growth performance when castrating cattle upon entry to the feedlot. Study Description:Intact bulls were sourced from the Southeastern U.S. and received at the Kansas State University Beef Stocker Unit. After backgrounding, 700-lb bulls were castrated using various techniques, including banding, banding with splitting of the distal scrotum, use of the Henderson Tool, and use of a burdizzo clamp. A group of intact bulls served as a negative control group. Weights were obtained at regular intervals throughout the 56-day study to quantify and compare growth performance. Results:The day 0 to day 56 average daily gain (ADG) showed no difference between treatment groups (P= 0.0643) but there was a trend for the Henderson group to gain at a lower rate than all other treatment groups. All other groups ended the 56-day study period with similar ADG. In addition, a trend was found for cattle castrated using the Henderson Tool to exhibit a lower activity time per hour than the other study groups for much of the day on average, as well as a greater number of minutes per hour ruminating on average. Jaw movement recorded as rumination was thought to be teeth grinding due to pain response and the lower amount of activity time would support this assessment. While the burdizzo group performed the best of all castrated groups, the labor-intensive process associated with applying the burdizzo clamp is not practical for cattle of this size. Cattle castrated using the band and band-cut methods performed better than those castrated using the Henderson Tool. The results of this study indicate that any castration technique that is surgical in nature is not ideal for castrating cattle at the feedlot. The Bottom Line:Use of a latex band for castrating cattle at entry to the feedlot appears to be the technique least detrimental to growth performance.
Keywords: feedlot; castration; performance